Retailer's make-or-buy decision for remanufactured products under in-house yield uncertainty - Niu, Baozhuang; Bao, Jinxiao; Cao, Bin (Omega (Oxford), 2022)
•Retailer's make-or-buy decision for remanufactured products is studied considering yield uncertainty.•High consumer's valuation of the remanufactured product may be harmful for the environment.•High consumer's valuation of the remanufactured product might hurt the 3PR's profit.•Win-win-win situations can be achieved if the retailer purchases from a 3PR. Remanufacturing is a sustainable practice, as it can save resources and alleviate environmental pollution. However, the production process can be subject to yield uncertainty if the manufacturer has limited remanufacturing capability. This study considers a retailer that sells both new and remanufactured products simultaneously. The retailer can either produce the remanufactured product in-house under yield uncertainty (Scenario I), or remove this uncertainty by relying on a third-party remanufacturer (Scenario O). We investigate the retailer's make-or-buy decision under in-store competition (between new and remanufactured products) and find that, remarkably, consumers’ high valuation of the remanufactured product induces the retailer to order an increased quantity of new products in both Scenarios O and I. In addition, we find that the retailer can obtain a higher profit in Scenario O because the new product supplier will strategically lower the wholesale price owing to the intensified supply competition, which could also benefit the new product supplier and, hence, achieve a win–win situation.